The effect of wordwall educational game-based learning media on interest in learning natural sciences (Indonesian Institute for Counseling, Education and Theraphy, 2023)
This research was conducted to determine the effect of the use of learning media based on wordwall educational games on interest in learning science in class IV B students. This research is a quantitative study using a survey method. Researchers used a questionnaire as a data collection technique in this study. The population in this study were students of class IV B at SDN Duri Kepa 03, which consisted of 32 students. The data collection technique in this study was a questionnaire. Determination of the hypothesis in this study using a partial test or t test. The results of the hypothesis were obtained based on the partial test or t test, namely tcount 12,673 > ttable 2,042 with a significance value of 0.000 <0.05. The results of these calculations prove that H0 is rejected and H1 is accepted which means that there is a positive influence between Wordwall Educational Game-Based Learning Media (X) on Learning Interest (Y).